BIM deficiency differentially impacts the function of kidney endothelial and epithelial cells through modulation of their local microenvironment - Sheibani, Nader (American Physiological Society, 2012)
The extracellular matrix (ECM) acts as a scaffold for kidney cellular organization. Local secretion of the ECM allows kidney cells to readily adapt to changes occurring within the kidney. In addition to providing structural support for cells, the ECM also modulates cell survival, migration, proliferation, and differentiation. Although aberrant regulation of ECM proteins can play a causative role in many diseases, it is not known whether ECM production, cell adhesion, and migration are regulated in a similar manner in kidney epithelial and endothelial cells. Here, we demonstrate that lack of BIM expression differentially impacts kidney endothelial and epithelial cell ECM production, migration, and adhesion, further emphasizing the specialized role of these cell types in kidney function. Bim −/− kidney epithelial cells demonstrated decreased migration, increased adhesion, and sustained expression of osteopontin and thrombospondin-1 (TSP1). In contrast, bim −/− kidney endothelial cells demonstrated increased cell migration, and decreased expression of osteopontin and TSP1. We also observed a fivefold increase in VEGF expression in bim −/− kidney endothelial cells consistent with their increased migration and capillary morphogenesis. These cells also had decreased endothelial nitric oxide synthase activity and nitric oxide bioavailability. Thus kidney endothelial and epithelial cells make unique contributions to the regulation of their ECM composition, with specific impact on adhesive and migratory properties that are essential for their proper function.